Python Web Scraping for Threat Intelligence - Arya Adhi Nugraha; Domy Kristomo (LPPM STIKOM Tunas Bangsa, 2024)
The relentless evolution of cyber threats poses significant challenges to organizations striving to maintain robust cybersecurity defenses. In this context, the effective gathering and analysis of threat intelligence data play a crucial role in enhancing situational awareness and informing proactive security measures. This journal entry explores the utilization of Python web scraping techniques for threat intelligence purposes, with a focus on extracting valuable insights from the Cybersecurity and Infrastructure Security Agency (CISA) website. Through the development and implementation of a Python script for web scraping, the process of systematically gathering threat intelligence data is examined, highlighting the efficacy of automation in streamlining the collection and analysis of real-time threat data. The results demonstrate the effectiveness of the Python script in facilitating the rapid aggregation of threat intelligence from diverse online sources, providing security professionals with actionable insights to strengthen their cybersecurity defenses. Additionally, considerations regarding the ethical and legal implications of web scraping are addressed, emphasizing the importance of responsible data collection practices. Overall, this exploration of Python web scraping for threat intelligence underscores its potential as a valuable tool for enhancing cybersecurity resilience in the face of evolving cyber threats.